Dickkopf-3: Current Knowledge in Kidney Diseases - Fang, Xiangdong; Hu, Jing; Chen, Yanxia; Shen, Wen; Ke, Ben (Frontiers in Physiology, 2020)
Abstract Dickkopf-related protein 3 (DKK3) is a secreted glycoprotein that has been implicated in the pathogenesis of a variety ofvarious diseases. Recent evidence suggests that urinary DKK3 may serve asbe a potential biomarker for monitoring kidney disease progression and assessing the effects of interventions. We review the biological role of DKK3 as an agonist in chronic kidney disease (CKD) and autosomal dominant polycystic kidney disease (ADPKD) and as an antagonist in idiopathic membranous nephropathy (IMN). In addition, we present the clinical applications of DKK3 in acute kidney disease and tubulointerstitial fibrosis, and suggesting that urine DKK3 may asbe a potential biomarker for acute kidney disease and CKD. Further research into the mechanism of DKK3 and its use as a diagnostic tool, alone or in combination with other biomarkers, could prove clinically useful for better understanding the pathology of kidney diseases and improving early detection and treatment.